The Role of Intellectual Intelligence and Corporate Governance on Earnings Quality: A Company Size as Moderator Approach - Wijaya, Rico; Murnidayanti, Scheilla Aprilia; Purba, Marissa Rebecca Gabriella; Prastio, Ridho (Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to examine the effect of intellectual capital and corporate governance on earnings quality, with firm size as a moderating variable. The sample in this study consists of 47 companies included in the LQ45 index during the 2021–2023 period. Data were analyzed using a quantitative approach with WarpPLS 8.0 software. The results show that intellectual capital and the audit committee have a significant effect on earnings quality, while the independent board of commissioners and joint board meetings do not have a significant effect. The moderation test indicates that firm size does not moderate the relationship between intellectual capital, independent commissioners, audit committees, or joint board meetings and earnings quality. These findings highlight the importance of intellectual capital and the audit committee in improving earnings quality, while firm size does not strengthen these relationships. This study provides implications for company management and stakeholders to pay more attention to intellectual aspects and internal supervision in maintaining the integrity of financial reporting.